Histopathological Changes in the Liver, Heart and Kidneys Following Malayan Pit Viper (Calloselasma rhodostoma) Envenoming and the Neutralising Effects of Hemato Polyvalent Snake Antivenom - Wipapan Khimmaktong; Nazmi Nuanyaem; Nissara Lorthong; Wayne C. Hodgson; Janeyuth Chaisakul (Toxins, 2022)
Calloselasma rhodostoma (Malayan pit viper) is a medically important snake species that is widely distributed across Southeast Asia. Systemic coagulopathy causing severe haemorrhage and local tissue injury is commonly observed following C. rhodostoma envenoming. However, nephrotoxicity and congestive heart failure were previously reported in a patient who had a long length of hospital stay. In this study, we determined the effect of C. rhodostoma envenoming on cardiovascular disturbances and the associated morphological changes in the liver, heart and kidneys using animal models. We also evaluated the efficacy of Hemato polyvalent antivenom (HPAV; Queen Saovabha Memorial Institute (QSMI) of the Thai Red Cross Society, Thailand) in neutralising the histopathological effects of C. rhodostoma venom. The intravenous (i.v.) administration of C. rhodostoma venom (1000 µg/kg) caused a rapid decrease in mean arterial pressure (MAP) followed by complete cardiac collapse in anaesthetized rats. Moreover, the intraperitoneal (i.p.) administration of C. rhodostoma venom (11.1 mg/kg; 3 × LD50) for 24 h caused cellular lesions in the liver and heart tissues. C. rhodostoma venom also induced nephrotoxicity, as indicated by the presence of tubular injury, interstitial vascular congestion and inflammatory infiltration in the whole area of the kidney. The administration of HPAV, at manufacturer-recommended doses, 15 min prior to or after the addition of C. rhodostoma venom reduced the extent of the morphological changes in the liver, heart and kidneys. This study found that experimental C. rhodostoma envenoming induced cardiovascular disturbances, hepatotoxicity and nephrotoxicity. We also highlighted the potential broad utility of HPAV to neutralise the histopathological effects of C. rhodostoma venom. The early delivery of antivenom appears capable of preventing envenoming outcomes.